Analysis of CYP2D6 Allele Frequencies and Identification of Novel SNPs and Sequence Variations in Sardinians. (5th November 2013) - Falzoi, Matteo; Pira, Luigi; Lazzari, Paolo; Pani, Luca
Abstract : The CYP2D6 enzyme is involved in the metabolism of many commonly prescribed drugs. The presence of polymorphisms in the CYP2D6 gene may modulate the enzyme level and activity affecting individual responses, to pharmacological treatment in drug level, response and adverse reactions. Aims. This study aimed to analyze the determination of allele frequencies in Sardinians and the comparison to frequencies found in the Caucasian Population. Methods and Materials. We used a Long PCR strategy coupled to direct genomic DNA sequencing analysis. An amplification allele-specific was carried out to infer the correct allelic phase. The TaqMan Gene Copy Number Assay (Applied Biosystems) was used to verify the presence of gene deletions/multiplications. Results and Conclusions. Our results indicated that CYP2D6 allele frequencies in Sardinians differed from those previously detected in the Caucasian Population. Moreover, three new SNPs and four novel haplotypes were identified.